Chiral Cu(II)‐N4 Complex Catalyzed Asymmetric Aza‐Henry Reaction and Its Application in the Synthesis of β‐Diamine. Issue 14 (19th May 2017) - Menapara, Tusharkumar; Tak, Rajkumar; Chinnaraja, E.; Kureshy, Rukhsana I.; Patel, Parth; Khan, Noor‐ul H.
Abstract: ChiralCu(II)‐L3 complex was generated In situ to catalyze the asymmetric aza‐Henry reaction of various isatin derived N ‐Boc ketimines with nitromethane, nitroethane and 1‐nitropropane as nucleophiles at room temperature. High yield (up to 84 %) and excellent chiral induction (ee, up to 99 %) of β ‐nitroamine was obtained in 13 h. The β ‐nitroamine(1 g) was conveniently hydrogenated to enantiomerically pure ( S )‐ β ‐diamine in good yield and high enantioselectivity. The kinetic investigation was undertaken to understand the reaction mechanism of the catalytic aza‐Henry reaction usingCu(II)‐L3 as catalyst, with nitromethane and isatin N ‐Boc ketimine(1 g) as a representative substrate. Abstract : Cu(II)‐N4 catalyzed enantioselective aza‐Henry reaction of isatine derived N ‐Boc ketimine was reported in this study. Catalyst Cu(II)‐L3 afforded excellent enantioselectivity (up to 99 %) and good yield (up to 84 %) with nitromethane. Moderate yield (up to 75 %) and diastereoselectivity (up to 93:07) with excellent enantioselectivity (up to 95 %) was achieved in corresponding products with nitroethane and 1‐nitropropane. β ‐nitroamine is successfully reduced to the corresponding β ‐diamine. A probable mechanism based on kinetic study is proposed.